Revolutionize Small-Scale Retail Supply Chains: Integrating Logistics 5.0 for Nanostores in the Smart Economy - Ortega-Jimenez, Cesar H; Melgar-Martínez, Narciso A; Sabillon Palomeque, Dany N. (LACCEI, 2025)
This study investigates the impact of Logistics 5.0 on small-scale retail supply chains, focusing on enhancing operational efficiency, customer experience, and adaptability within nanostores. The research explores the integration of AI-driven inventory management and IoT-enabled supply chains in the context of the smart economy. A systematic review of literature was conducted to analyze the implementation of Logistics 5.0 technologies, with data collected from multiple databases, including Scopus, Web of Science, and JSTOR. The findings reveal a 77% reduction in stockouts, a 60% decrease in overstocking, and a 21.7% increase in sales following the integration of Logistics 5.0. These results confirm the proposition that Logistics 5.0 enhances supply chain efficiency (Proposition 1), improves customer experience through real-time data and AI (Proposition 2), and fosters adaptability through human-machine collaboration (Proposition 3). The research offers actionable insights for nanostore retailers and policymakers, demonstrating how Logistics 5.0 can enhance access to goods in underserved communities, improving economic resilience and sustainability within small-scale retail sectors. Future studies could expand these findings by investigating the broader social and environmental implications of Logistics 5.0 in small retail contexts, paving the way for sustainable practices in smart retail ecosystems.